Case Report: Phenotype-Driven Diagnosis of Atypical Dravet-Like Syndrome Caused by a Novel Splicing Variant in the SCN2A Gene - Sharkov, Artem; Sparber, Peter; Stepanova, Anna; Pyankov, Denis; Korostelev, Sergei; Skoblov, Mikhail (Frontiers in Genetics, 2022)
Febrile associated epileptic encephalopathies are a large genetically heterogeneous group that is associated with pathogenic variants in SCN1A, PCDH19, SCN2A, SCN8A and other genes. The disease onset ranges from neonatal or early onset epileptic encephalopathy to late onset epilepsy after 18 months. Some etiology-specific epileptic encephalopathies have target therapy which can serve as a clue for the correct genetic diagnosis. We present genetic, clinical, electroencephalographic and behavioral features of a 4-years-old girl with epileptic encephalopathy related to a de novo intronic variant in SCN2A gene. Initial NGS analysis revealed a frameshift variant in KDM6A gene and a previously reported missense variant in SCN1A. Due to lack of typical clinical signs of Kabuki syndrome we performed X-chromosome inactivation that revealed nearly complete skewed inactivation. Segregation analysis showed that the SCN1A variant was inherited from a healthy father. The proband had resistance to multiple antiseizures medications but responded well to sodium channel inhibitor Carbamazepine. Reanalysis of NGS data by a neurogeneticist revealed a previously uncharacterized heterozygous variant c.1035-7A>G in the SCN2A gene. Minigene assay showed that c.1035-7A variant activates a cryptic intronic acceptor site which leads to 6 nucleotide extension of exon 9 (NP_066287.2:p.(Gly345_Gln346insTyrSer). SCN2A encephalopathy is a recognizable severe phenotype. Its electro-clinical and treatment response features can serve as a hallmark. In such patient’s reanalysis of genetic data is strongly recommended in case of negative or confliction results of DNA analysis.